Bioinspired short peptide hydrogel for versatile encapsulation and controlled release of growth factor therapeutics. (December 2021) - Hiew, Shu Hui; Wang, Jun Kit; Koh, Kenrick; Yang, Haibo; Bacha, Abbas; Lin, Junquan; Yip, Yun Sheng; Vos, Marcus Ivan Gerard; Chen, Liyan; Sobota, Radoslaw M.; Tan, Nguan Soon; Tay, Chor Yong; et al.
Abstract: A short bioinspired octapeptide, GV8, can self-assemble under mild conditions into biodegradable supramolecular physical hydrogels with high storage modulus and good biocompatibility. GV8 hydrogels can encapsulate both single or multiple macromolecular protein-based therapeutics in a simple one-pot formulation manner, making it a promising candidate to address challenges faced by existing synthetic polymer or peptide hydrogels with complex gelation and drug-encapsulation processes. Alongside its versatility, the hydrogel exhibits concentration-dependent storage modulus and controlled drug-release action. We demonstrate that GV8 hydrogels loaded with adipose-derived mesenchymal stem cells (ADMSC) secretome remain mechanically robust, and exhibit promising potential for wound healing applications by preserving secretome activity while maintaining a constant supply of ADMSC secretome to promote epithelial cell migration. Overall, our work highlights the potential of GV8 peptide hydrogel as a versatile and safe carrier for encapsulation and delivery of macromolecular therapeutics. Statement of significance: Supramolecular peptide hydrogels are a popular choice for protein-based macromolecular therapeutics delivery; however, despite the development of abundant hydrogel systems, several challenges limit their adaptability and practical applications. GV8 short peptide hydrogel circumvents these drawbacks and demonstrates the ability to function as a versatile growth factor (GF) encapsulant. It can encapsulate precise concentrations of complex adipose-derived mesenchymal stem cells secretome mixtures with a one-pot formulation approach and perform controlled release of GFs with preserved activity without compromising the self-assembly and mechanical properties of the hydrogel's supramolecular network. The significance of GV8 hydrogel lies in its gelation simplicity and versatility to encapsulate and deliver macromolecular therapeutics, thus representing a promising biomaterial for regenerative medicine applications. Graphical abstract: Image, graphical abstract